2021
DOI: 10.14202/vetworld.2021.1389-1397
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity among two native Indian chicken populations using cytochrome c oxidase subunit I and cytochrome b DNA barcodes

Abstract: Background and Aim: India has large varieties (recognized, unrecognized) of native chickens (Desi) scattered throughout the country, managed under scavenging system different from commercial chicken breeds. However, they are less investigated for genetic diversity they harbor. The present study was planned to evaluate genetic diversity among two native chicken populations of North Gujarat (proposed Aravali breed) and South Gujarat (Ankleshwar breed). Aravali chicken, a distinct population with unique character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
2
1
2
Order By: Relevance
“…Although ISM ecotypes have a relatively wider length range (563-611 bp) compared to TA ecotype (570-607 bp). The average sequence length was shorter than what was reported by Xun-he et al (2016) 28 31 found that the sequence length of cytochrome c oxidase subunit I length for two native Indian chicken breeds averaged 608 and 756 bp. However, it is also important to note that due to the fact that the molecular evolution rate fluctuate among various segments of the genome and across taxa, there no species-specific standard sequence length.…”
Section: Resultscontrasting
confidence: 54%
See 2 more Smart Citations
“…Although ISM ecotypes have a relatively wider length range (563-611 bp) compared to TA ecotype (570-607 bp). The average sequence length was shorter than what was reported by Xun-he et al (2016) 28 31 found that the sequence length of cytochrome c oxidase subunit I length for two native Indian chicken breeds averaged 608 and 756 bp. However, it is also important to note that due to the fact that the molecular evolution rate fluctuate among various segments of the genome and across taxa, there no species-specific standard sequence length.…”
Section: Resultscontrasting
confidence: 54%
“…To our surprise, both ecotypes have the same number of sites 548 bp (Table 1) 31 found that the total number of sites of two native Indian chicken populations was 596 and 647 of which merely 3 and 4 polymorphic sites were detected. Yu-Shi et al (2011) 33 on 26 individuals of two newly discovered chicken breeds found only 10 variation sites, of which only 6 sites were single polymorphism sites while 4 were simple information sites.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Günümüzde, PCR ile DNA analizi, ilgi konusu genlerin bölgelerinin amplifiye edilmesine izin verdiği için, türlerin tanımlanmasında rutin olarak kullanılan bir yöntem haline gelmiştir [25][26][27] .…”
unclassified
“…Türlerin tanımlanmasında uluslararası olarak önerilen iki mitokondriyal bölge bulunmaktadır: sitokrom B (CYTB) ve sitokrom c oksidaz alt birim I geni (COI). CYTB ve COI bölgeleri evrensel primerler tarafından tanınan bazı stabil dizilere, kimliklendirmeyi sağlayacak birtakım dizi çeşitliliklerine sahiptir, bu nedenle bu nükleotid dizileri türe özgü bilgiler içerir 9,27 .…”
unclassified